Hypolipidemic Effect and Mechanism of Bifidobacterium animalis NX-6 on a Zebrafish Model of Hyperlipidemia - HE Yingxi, XU Xinzhu, LIN Shuxian, SHENG Wen, XU Suhua, GUO Lina (Shipin Kexue)
Objective: To analyze the characteristics of Bifidobacterium animalis NX-6 and to explore its lipid-lowering mechanism in the model organism zebrafish using metabolomics. Methods: The growth curve of NX-6 was plotted, and the cell morphology was observed using field emission-scanning electron microscopy (FE-SEM). Its tolerance to simulated gastrointestinal conditions was assessed. Its safety and potential benefits were evaluated at the genetic level through whole-genome sequencing. Untargeted and targeted metabolomics analysis was conducted based on liquid chromatography-mass spectrometry (LC-MS) to identify metabolites produced by NX-6, focusing on key lipid-lowering metabolites. Hyperlipidemia in zebrafish was induced by feeding a high-fat diet, and Oil Red O staining was used to observe lipid accumulation. This study evaluated the lipid-lowering effect and mechanism of NX-6 and its key metabolites. The hypolipidemic effect of the key metabolite indole-3-acetic acid was evaluated on hyperlipidemic zebrafish. Results: Compared with B. animalis BB12, B. animalis NX-6 demonstrated significantly higher tolerance to artificial gastrointestinal fluids. The genome of NX-6 lacked virulence genes but contained abundant lipid and tryptophan metabolism gene clusters. NX-6 significantly reduced total cholesterol and triglyceride levels in hyperlipidemic zebrafish (P < 0.001). Indole-3-carboxylic acid and 2-indole ketone were significantly increased in the fermentation supernatant of NX-6 compared with BS medium. Following NX-6 treatment, the content of indole-3-carboxylic acid in zebrafish significantly rose (P < 0.001). Indole-3-carboxylic acid notably decreased total cholesterol and triglyceride levels in hyperlipidemic zebrafish (P < 0.001). Conclusion: B. animalis NX-6 reduced lipid accumulation in hyperlipidemic zebrafish through its metabolite indole-3-carboxylic acid.